How do artificial sweeteners affect your health? - Bezsheiko, Vitaliy (Psychosomatic Medicine and General Practice, 2017)
According to a new analysis of long-term studies, they increase the risk of obesity, arterial hypertension, stroke, cardiovascular events, and type 2 diabetes.